Intravenous golimumab in rheumatoid arthritis. (July 2014) - Cohen, Marc D; Keystone, Edward C
<x xml:space="preserve">Abstract</x> Intravenous golimumab in a dosage of 2 mg/kg, initially given every 4 weeks but then every 8 weeks, in addition to methotrexate, is effective in the treatment of patients with rheumatoid arthritis. This weight-based infusion is administered over thirty minutes with an acceptable safety profile. Since it is a relatively new formulation, more time will be required to assess its specific role in the rheumatologists' armamentarium and to appreciate more fully its long-term safety.